2014
DOI: 10.3138/ptc.2012-57
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Approaches to Balance Assessment in Physical Therapy Practice for Elderly Inpatients of a Rehabilitation Hospital

Abstract: Purpose: Balance is a critical modifiable risk factor for falls in older adults. The purpose of this study was to identify the physiotherapy assessment tools used to evaluate balance in clinical practice and to determine the components of balance assessed through the use of standardized and/or other measures. Methods: A retrospective chart review was performed on 250 patients aged 65 and older undergoing in-patient rehabilitation with a clinical diagnosis associated with a balance impairment (stroke, musculosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
1
25
0
2
Order By: Relevance
“…Dessa forma, vem sendo frequentemente utilizado para examinar a mobilidade funcional em idosos. 20,21 O teste TUG foi realizado de acordo com Podsiadlo e Richardson. 21 Com o voluntário sentado em uma cadeira, o avaliador opera o comando verbal para que o mesmo se levante sem ajuda dos braços, ande 3 metros (demarcados), vire, caminhe de volta os 3 metros e sente novamente na cadeira.…”
Section: Avaliação Funcional: Teste Timed Up and Gounclassified
See 1 more Smart Citation
“…Dessa forma, vem sendo frequentemente utilizado para examinar a mobilidade funcional em idosos. 20,21 O teste TUG foi realizado de acordo com Podsiadlo e Richardson. 21 Com o voluntário sentado em uma cadeira, o avaliador opera o comando verbal para que o mesmo se levante sem ajuda dos braços, ande 3 metros (demarcados), vire, caminhe de volta os 3 metros e sente novamente na cadeira.…”
Section: Avaliação Funcional: Teste Timed Up and Gounclassified
“…Esse fato pode ter contribuído para que aqueles autores encontrassem sujeitos desempenhando o teste de forma mais lenta. 9,20 A baixa autoeficácia encontrada em idosos ao subir e descer escadas, em estudos que os comparam a jovens, tem sido relacionada com frequência à falta de confiança sobre as capacidades motoras, além da presença de déficits motores e mecânicos. 1,[25][26][27] A hipótese do presente estudo foi que idosas com preocupação em cair teriam o primeiro pico da Fz menor com relação a idosas sem preocupação.…”
Section: Artigo Original / Original Articleunclassified
“…Multiple surveys of Canadian balance assessment practices have found that less than half of participating physiotherapists reported regularly assessing reactive balance when treating adults with balance impairment [ 21 , 22 ]. One retrospective study of balance assessment among adults aged 65 years and older who were admitted to a Canadian rehabilitation hospital in 2009–10 determined that just 2% of randomly-selected records included an explicit assessment of reactive balance [ 23 ]. One study exploring factors influencing reactive balance measurement identified multiple barriers.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Furthermore, to be sedentary or have the presence of any disease related to vestibular system also can compromise the performance of the postural control and thus, increases the risk of falls. Some studies have investigated postural control in elderly people with different health conditions, (5,6) but few reported difference between those with vestibular disorder related to two different groups (active and sedentary elderly) based on balance parameters from a force platform measurement.…”
Section: Introductionmentioning
confidence: 99%